2002
DOI: 10.1097/00042737-200204000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Establishing patient preferences for gastroenterology clinic reorganization using conjoint analysis

Abstract: The present Department of Health recommendations and the Patients' Charter are too simplistic and do not take into account patient preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…However, one survey of a gastroenterology clinic showed that patients placed a similar value on waiting time for investigation and waiting for the first appointment: 4 a clinic that had a two-month wait for appointment, but offered immediate investigation was preferable to one with a two-week wait for appointment but a three-month wait for investigation. The authors suggest that to focus just on 'wait to first appointment' is too simplistic and does not take account of patient preferences.…”
Section: Waiting Time and Appointmentsmentioning
confidence: 99%
“…However, one survey of a gastroenterology clinic showed that patients placed a similar value on waiting time for investigation and waiting for the first appointment: 4 a clinic that had a two-month wait for appointment, but offered immediate investigation was preferable to one with a two-week wait for appointment but a three-month wait for investigation. The authors suggest that to focus just on 'wait to first appointment' is too simplistic and does not take account of patient preferences.…”
Section: Waiting Time and Appointmentsmentioning
confidence: 99%
“…In the last few years its use has become increasingly common in health economics. Studies have used stated preference modeling to predict participation rates of chickenpox vaccination by parents [4], to model migraine medication choice by patients [5], to model choice of health plans [6][7][8] value of magnetic resonance imaging for investigation of knee injuries [9], to estimate patient preferences for clinical waiting times [10], to estimate demand for hospital services [11], to estimate demand for in vitro fertilization [12], to elicit preferences for miscarriage management [13], to assess preferences in the doctor-patient relationship [14], and to measure time preferences for health and willingness to pay for longevity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Adopting measures to improve these two main problems would have a high probability of reducing the problem rate encountered by our patients [14]. Generally speaking, waiting times are an important determinant for patient satisfaction in varying clinical contexts emergency, pediatric care, colonoscopy appointments, or primary care medical appointments [15][16][17][18]. Data from the research of Moayyedi et al [16] underline the importance of waiting time until the appointment when carrying out complementary gastrointestinal examinations.…”
Section: Discussionmentioning
confidence: 99%